2021
DOI: 10.3390/nu13030864
|View full text |Cite
|
Sign up to set email alerts
|

Is a Four-Week Ketogenic Diet an Effective Nutritional Strategy in CrossFit-Trained Female and Male Athletes?

Abstract: This single-arm interventional study examined the effect of a 4-week ketogenic diet (KD) on aerobic capacity and discipline-specific performance in female (n = 11) and male (n = 11) CrossFit-trained athletes. The participants performed incremental cycling (ICT) and Fight Gone Bad (FGB) tests after consuming a customary diet and a KD. Pre- and post-ICT exercise blood samples were also analysed. Consuming a KD had a slight impact on aerobic capacity and no relevant effect on CrossFit-specific performance. In fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 64 publications
0
35
0
1
Order By: Relevance
“…In another study, the K-LCHF diet was effective in extending some older athletes’ professional life by controlling or losing weight [ 9 ]. Another study analyzed gender differences after adopting the K-LCHF diet for four weeks and found a reduction in VO 2 max in women after the intervention, which was not observed in men [ 31 ]. We found that body mass was significantly decreased after the K-LCHF diet intervention in seven studies, but no significant changes in VO 2 max were observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, the K-LCHF diet was effective in extending some older athletes’ professional life by controlling or losing weight [ 9 ]. Another study analyzed gender differences after adopting the K-LCHF diet for four weeks and found a reduction in VO 2 max in women after the intervention, which was not observed in men [ 31 ]. We found that body mass was significantly decreased after the K-LCHF diet intervention in seven studies, but no significant changes in VO 2 max were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The screening process was divided into two phases: a preliminary selection by title and abstract only, and a second phase of screening the full text of the remaining articles. Articles that met the following criteria were included: (1) randomized controlled intervention trial or controlled intervention trial or crossover trial in endurance athletes (including professional athletes and individuals who participated in endurance exercise as their hobby); (2) a LCHF diet with less than 10% CHOs is considered a K-LCHF diet [ 31 , 32 ]; (3) comparison of the effects of the K-LCHF diet with those of the non-LCHF diet; (4) performed graded exercise test (GXT); 5) reported daily nutrition intake based on food diaries or recalls; (5) endurance training was defined as long-duration continuous sustain moderate or submaximal intensity exercise of 5 min to 4 h [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Fleming et al observed that a 6-week high-fat diet (61% fat, 8% carbohydrate) resulted in a reduced peak and mean power during a Wingate test compared with a control diet [ 68 ]. More recently, a study conducted in CrossFit athletes revealed that a 4-week KD induced no beneficial effects on CrossFit-specific performance (assessed through a workout including jumps, push presses and rowing, among other exercises) and even resulted in an impaired cardiorespiratory fitness (lower peak oxygen uptake) in women [ 69 ].…”
Section: Effects Of Combining Ketogenic Diets With Resistance Training On Strength and Power Performance In Trained Individualsmentioning
confidence: 99%
“…After 4 weeks of a KD, female mice displayed higher fat-to-lean mass ratios and decreased cardiac function compared to chow-fed controls [ 26 ]. In human studies, females fed with a 4 week KD showed decreased time to exhaustion during a cycling test in a cross-over design [ 27 ], whereas 4 weeks of a KD led to decreased exercise performance in females but not in males [ 28 , 29 ]. These results suggest that females may be more adversely affected by changes in ketone body metabolism than males.…”
Section: Introductionmentioning
confidence: 99%